The promise and challenges of the fourth industrial revolution (4IR). Issue 1 (10th April 2023) - Datta, Pratim
The fourth Industrial Revolution is upon us. Yet not many students understand its evolution or impacts. This teaching case looks at socio-technical evolution from 1IR (First Industrial Revolution) to 4IR (Fourth Industrial Revolution). The teaching case concludes by exemplifying 4IR's promises and perils with a mini case on how 4IR that quietly helped the COVID-19 vaccine development can also pose cyberthreats and erode privacy.